Broadening of horizons: a review of blockchains' influence on EHRs development trend. (16th April 2023) - Babu, G. Kalivaraprasanna; Thiyagarajan, P.
Electronic health records (EHR) improves the quality and effectiveness of healthcare. The introduction of blockchain opens up new paths in the development trend of EHR. This review aims to find the developmental trends of the EHR, blockchain-based EHR and its impact on EHR evolution. A total of 85 articles published in 2015 to 2021 were selected, addressing the general development of EHR. Development aspects of EHR addressed by each were analysed, hence tracing the path taken by each. Researchers for the betterment of traditional EHR sought to address usability, adaptability, needs of specialised areas, and patient inclusivity in the workflow, while stressing the application of EHR for predictive analysis, preventive healthcare, population health, etc. The literature on blockchain-based EHR contributed to mitigating the interoperability, promoting data sharing and patient-centric records. While traditional EHR deepens their reach into healthcare, blockchain-based EHR broadens the reach of healthcare itself.